2004
DOI: 10.1002/ird.134
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of irrigation scheduling parameters using the growing degree days concept: application to a potato crop

Abstract: An accurate irrigation scheduling methodology is necessary in crops with high water stress sensitivity and production cost. This involves the estimation of the scheduling parameters related with crop water requirements during phenological stages under different irrigation application systems. This paper presents several models to represent the parameters of irrigation scheduling based on growing degree days (GDD) such as: management allowed soil water depletion (MAD), rooting depth (R d ) and crop coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 13 publications
0
17
0
7
Order By: Relevance
“…For calculating the growing degree days index (GDDI) for the purpose of modifying the biomass yield caused by the damages due to frost, the AquaCrop model uses the maximum and minimum daily temperatures (Raes et al, 2006), which is an effective index in crop growth and its phenologic stage. Daily growing degree days (GDD) which has been calculated by using the following equations (Ojeda-Bustamante et al, 2004), showed that growing degree days index in Honam site in the 2 growing seasons are 1211 and 1042, respectively. These values belong to the period of September 23 to July 7.…”
Section: Weather Parametersmentioning
confidence: 99%
“…For calculating the growing degree days index (GDDI) for the purpose of modifying the biomass yield caused by the damages due to frost, the AquaCrop model uses the maximum and minimum daily temperatures (Raes et al, 2006), which is an effective index in crop growth and its phenologic stage. Daily growing degree days (GDD) which has been calculated by using the following equations (Ojeda-Bustamante et al, 2004), showed that growing degree days index in Honam site in the 2 growing seasons are 1211 and 1042, respectively. These values belong to the period of September 23 to July 7.…”
Section: Weather Parametersmentioning
confidence: 99%
“…Throughout both irrigation seasons, the potato crop was monitored once per week to determine crop growth stages using the Biologische Bundesarstalt Bundessoztenamt and Chemical Industry scale (BBCH) (Hack et al, 1993). The duration of each crop stage was determined using growing degree days (GDD) (Ojeda‐Bustamante et al, 2004). Yield and harvest index (HI) were determined for each irrigation treatment after manual harvest of 18 m 2 from the center of the experimental plot (60 m 2 ) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…There are different indirect methods to estimate crop water requirements (Radiation, Blaney-Criddle, PenmaneMonteith equations and Pan Evaporation) based on whether parameters, also direct information from usually one variable of the soilewatereplant system to estimate the soil water content such as the neutron probe and time-domain-reflectometry (TDR), or soil water tension in the soil by tensiometers or gypsum blocks. Nevertheless, all such devices present problems when they are used in large irrigation areas due to temporal and spatial variability of measurements and high costs of installation and management, in addition to sample alteration and low sampling volume (Ojeda-Bustamante, Sifuentes-Ibarra, Slack, & Carrillo, 2004).…”
Section: Introductionmentioning
confidence: 99%